Association of Maternal Anemia and Risk of Preterm Birth in Pregnant Women at Dr Ruth KM Pfau Civil Hospital Karachi - Batool, Misbah; Habib, Aneela; Bushra; Kumari, Devia; Usman, Marium; Rana, Faiza (Indus Journal of Bioscience Research, 2025)
Background: Anemia is a major public health problem in low- and middle-income countries, including pregnant women. It is linked to poor maternal and infant health outcomes, including preterm birth - a major cause of perinatal morbidity and death. But the link between maternal anemia and preterm birth is conflicting in various populations. Objective: To determine the association between maternal anemia and the risk of preterm birth in pregnant women. Methods: This prospective cohort study was conducted at the Department of Obstetrics and Gynaecology, Dr. Ruth K. M. Pfau Civil Hospital, Karachi from March 2025 to June 2025. A convenience sample of 94 pregnant women were recruited and assigned into anemic (n=47) and non-anemic (n=47) groups. Anemia was defined as hemoglobin levels